Ceftobiprole Perspective: Current and Potential Future Indications - Lupia, Tommaso (Antibiotics (Basel), 2021)
Ceftobiprole combines an excellent spectrum for community-acquired pneumonia (CAP) and hospital-acquired pneumonia (HAP) pathogens, with a low/medium MDR risk, and the β-lactams’ safety in frail patients admitted to the hospital in internal medicine wards which may be at high risk of adverse events by anti-MRSA coverage as oxazolidinones or glycopeptides. We aimed to report the available evidence regarding ceftobiprole use in pneumonia and invasive bacterial infections, shedding light on ceftobiprole stewardship. The clinical application and real-life experiences of using ceftobiprole for bloodstream infections, including infective endocarditis, are limited but nevertheless promising. In addition, extended-spectrum ceftobiprole activity, including Enterococcus faecalis, Enterobacteriaceae, and Pseudomonas aeruginosa, has theoretical advantages for use as empirical therapy in bacteremia potentially caused by a broad spectrum of microorganisms, such as catheter-related bacteremia. In the future, the desirable approach to sepsis and severe infections will be administered to patients according to their clinical situation, the intrinsic host characteristics, the susceptibility profile, and local epidemiology, while the “universal antibiotic strategy” will no longer be adequate.